Multiplying 2 term with 2 terms

#### (3a + 4b) × (2a + 3b)

= 3a × (2a + 3b) + 4b × (2a + 3b)

= 3a × 2a + 3a × 3b + 4b × 2a + 4b × 3b

= 6a
^{
2
}
+ 9ab + 8ba + 12b
^{
2
}

*
Since
*
*
ab
*
*
=
*
*
ba
*

= 6a
^{
2
}
+ 9ab + 8ab + 12b
^{
2
}

= 6a
^{
2
}
+ ab (9 + 8) + 12b
^{
2
}

= 6a
^{
2
}
+ 17 ab + 12b
^{
2
}

#### (x + 2) × (x + 4b)

= x × (x + 4) + 2 × (x + 4)

= x × x + 4 × x + 2 × x + 2 × 4

= x
^{
2
}
+ 4x + 2x + 8

= x
^{
2
}
+ x (4 + 2) + 8

= x
^{
2
}
+ 6x + 8

Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class